2010
DOI: 10.1186/2047-783x-15-s2-17
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunotherapy in asthma does not influence lymphocyte sensitivity to fas stimulation

Abstract: Background The resistance of T lymphocytes to Fas-mediated apoptosis is an important feature of atopic asthma. The only effective causative treatment of atopic diseases is immunotherapy. Clinical efficacy of sublingual immunotherapy (SLIT) has been already proven, but there is still limited number of studies on its influence on lymphocytes function. Objectives The aim of the study was to evaluate whether SLIT could restore the sensitivity of asthmatic T cells to undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It is now shown that Sublingual Immunotherapy (SLIT) is much safer than Subcutaneous Immunotherapy (SCIL), [2,[4][5][6][7] because it is noninvasive and in several studies it was shown that it reduces both symptoms and medical requirements [2,[8][9][10]. Some studies showed immunologic changes during SLIT such as increased Th1 to Th2 activities and increased T regulatory cytokine secretion [11][12][13][14], but other studies did not show significant effects [15][16][17]. Rye grass is the most common allergen in our area specially in children and youth and could affect activity and school works of sensitive patients [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is now shown that Sublingual Immunotherapy (SLIT) is much safer than Subcutaneous Immunotherapy (SCIL), [2,[4][5][6][7] because it is noninvasive and in several studies it was shown that it reduces both symptoms and medical requirements [2,[8][9][10]. Some studies showed immunologic changes during SLIT such as increased Th1 to Th2 activities and increased T regulatory cytokine secretion [11][12][13][14], but other studies did not show significant effects [15][16][17]. Rye grass is the most common allergen in our area specially in children and youth and could affect activity and school works of sensitive patients [18].…”
Section: Introductionmentioning
confidence: 99%